2019
DOI: 10.1080/13698575.2019.1602251
|View full text |Cite
|
Sign up to set email alerts
|

‘It can’t do any harm’: A qualitative exploration of accounts of participation in preventive health checks

Abstract: Assessing and managing risk are central to participation in preventive health checks, as the purpose is to identify adverse health behaviours and risk factors. Drawing on the cultural theory of risk, we explore why people without formal education participate in preventive health checks and discuss how this is related to their understandings of risk and health. With this aim, we conducted semistructured qualitative interviews with people without formal education who participated in the intervention study Check-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…This means that the assessment could point to healthrelated problems that patients may not have recognized as problematic. However, motivation for health behavioral change has generally been found to occur when patients experience symptoms affecting their quality of life and affected by conditions surrounding their everyday lives and to a lesser extent influenced by information about risk [10,[38][39][40][41]. Furthermore, although the TOF pilot study provided the patients with a risk profile and offered a digital health profile, which they were encouraged to look through to prepare for the health dialogue, we found that the risk profiles did not affect the health dialogues as such.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…This means that the assessment could point to healthrelated problems that patients may not have recognized as problematic. However, motivation for health behavioral change has generally been found to occur when patients experience symptoms affecting their quality of life and affected by conditions surrounding their everyday lives and to a lesser extent influenced by information about risk [10,[38][39][40][41]. Furthermore, although the TOF pilot study provided the patients with a risk profile and offered a digital health profile, which they were encouraged to look through to prepare for the health dialogue, we found that the risk profiles did not affect the health dialogues as such.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Our ndings, however, do not support this suggestion, given that patients in the health dialogues brought up other medical health problems despite the intended focus on prevention. Qualitative studies of complex preventive interventions have shown that participants ascribe different expectations to their participation than assumed in the intervention and that these expectations are based on their everyday lives [39]. Our study already includes interviews with participating patients with the purpose of examining patients' expectations and experiences with the health dialogue.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…This means that the assessment could point to health-related problems that patients may not have recognized as problematic. However, motivation for health behavioral change has generally been found to occur when patients experience symptoms affecting their quality of life and affected by conditions surrounding their everyday lives and to a lesser extent in uenced by information about risk [10,[37][38][39][40]. Furthermore, although the TOF pilot study provided the patients with a risk pro le and offered a digital health pro le, which they were encouraged to look through to prepare for the health dialogue, we found that the risk pro les did not affect the health dialogues as such.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Qualitative studies of complex preventive interventions have shown that participants ascribe different expectations to their participation than assumed in the intervention and that these expectations are based on their everyday lives [39]. Our study already includes interviews with participating patients with the purpose of examining patients' expectations and experiences with the health dialogue.…”
Section: Concluding Discussionmentioning
confidence: 99%